Visuomenės nuomonės veikimo sąlygos sovietinėje Lietuvoje - Klumbys, Valdemaras (Lietuvos istorijos studijos, 2007)
One of the main aims of the Soviet regime in Lithuania is to crush internal and external enemies. Discreditation of the enemy - creation of their negative image and opinion in the society is one of the means of that fight. Political changes after the death of Stalin and changes of the USSR international position forced KGB to use the means of psychological influence, pressure besides physical repression, actions of falsehood, discreditation, various provocations, and intimidation. In such a way, KGB wanted to hide political repression. In a struggle with inner enemies, KGB used the method of discreditation, which aims to damage authority, good name of an opponent, and trust of society in him by leaking out or interpreting negatively the facts of his life and activity in order to suppress their activity, lower the number of supporters and to justify the repression. The time of appearance of discreditable information, its form, and to what part of society it is designed is very important. In Soviet Lithuania, the discreditable information is related to the person’s past, his activity in independent Lithuania, during the first Soviet and Nazi occupation, and after the war period. Personal information, like diseases, love affairs, sexual orientations, crimes, and mistakes in the past was used also. After crushing armed resistance in 1953, anti-Soviet opposition turned into unarmed form of resistance. It is difficult to crush it with force; that is why every more important national, religious, and civil anti-Soviet action was followed by discreditation actions. There were a couple forms of discreditation actions - falsehood and slander campaign through press and spreading rumors, letters or petitions incited by KGB, criminalizations of political trials, putting dissent into mental hospitals. Those campaigns were carried out until the ninth decade, but during the rebirth period, they did not make any effect on public opinion. The biggest discreditation actions were carried against the biggest critics of the Soviet system - Lithuanian Catholic Church, dissidents, fighters for human rights and liberties, emigration organizations, and most active persons. The discreditation method was efficient just partly because KGB did not reach the main target - to make opposition end their anti-Soviet activity, although they overshadowed their good name, morale, and activity.